2022
DOI: 10.3390/ijms231911815
|View full text |Cite
|
Sign up to set email alerts
|

Association of MARC1, ADCY5, and BCO1 Variants with the Lipid Profile, Suggests an Additive Effect for Hypertriglyceridemia in Mexican Adult Men

Abstract: Epidemiological studies have reported that the Mexican population is highly susceptible to dyslipidemia. The MARC1, ADCY5, and BCO1 genes have recently been involved in lipidic abnormalities. This study aimed to analyze the association of single nucleotide polymorphisms (SNPs) rs2642438, rs56371916, and rs6564851 on MARC1, ADCY5, and BCO1 genes, respectively, with the lipid profile in a cohort of Mexican adults. We included 1900 Mexican adults from the Health Workers Cohort Study. Demographic and clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In this study we used exome-wide association analysis in over 500,000 individuals to identify several novel rare pLOFs variants in MARC1 with phenotypes similar to previously reported p.Ala165Thr (A165T) and p.Met187Lys (M187K) variants [11][12][13][14][15][16][17][18][19]. We showed p. A165T substitution in MARC1 causes protein instability, leading to the lower MARC1 protein levels in the livers of human carriers of MARC1 p.A165T variant, confirming this variant is a loss of function.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this study we used exome-wide association analysis in over 500,000 individuals to identify several novel rare pLOFs variants in MARC1 with phenotypes similar to previously reported p.Ala165Thr (A165T) and p.Met187Lys (M187K) variants [11][12][13][14][15][16][17][18][19]. We showed p. A165T substitution in MARC1 causes protein instability, leading to the lower MARC1 protein levels in the livers of human carriers of MARC1 p.A165T variant, confirming this variant is a loss of function.…”
Section: Introductionmentioning
confidence: 62%
“…These studies revealed several missense variants that are associated with lipid accumulation and NAFLD progression [3][4][5][6][7][8][9][10]. Recent genome-wide association studies discovered that common MARC1 missense variants (p. A165T, rs2642438 G>A and p.M187K, rs17850677 T>A) and several rare MARC1 putative loss of function (pLOF) variants (p.R200Ter, p.R305Ter) in humans are associated with decreased liver fat, lower blood ALT, lower alkaline phosphatase, reduced LDL and total cholesterol, as well as protection from all-cause of liver cirrhosis [11][12][13][14][15][16][17][18][19]. MARC1 (mitochondrial amidoxime-reducing component 1, known also as MOSC1 and MTARC1) is a molybdenum containing enzyme anchored on the outer mitochondria membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, it has been reported that the Mexican population is highly susceptible to the development of dyslipidemia [18]. The most common dyslipidemias in Mexico include hypoalphalipoproteinemia, followed by hypertriglyceridemia and hypercholesterolemia [19].…”
Section: Introductionmentioning
confidence: 99%